Fenomen w „martwym lustrze”. Poezja Josifa Brodskiego w kontekście ewolucji sztuki europejskiej - Nikadem-Malinowska, Ewa (Acta Polono-Ruthenica, 2004)
The presence of the ancient Greek culture as a source of ethics and aesthetics in the life of a contemporary European is norm. The European art, including literature, has drawn inspiration from Greece for so many centuries now. Joseph Brodsky felt its during his successure stay in Venice. His entire artistic road consists in analyzing and synthesizing particular centuries of art, great painters, musicians, poets and philosophers. The cultural heritage passed on to him constitu tes our common good. The evolution of the European art shows what kind of path each artist, aware of his/her origin and abilities, followed. The tendency to generalize, to think abstractively, expressing itself in phenomenologizing the elements of reality, grew and strengthened along with the thought that led the poet to peaks of philosophy and artistry. To be able to verbalize this thought, reflected in a „dead mirror” is given to few.